2019
DOI: 10.1161/circulationaha.119.039996
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin and Cardiovascular Outcomes in Patients With Type 2 Diabetes Mellitus and Previous Myocardial Infarction

Abstract: Background: Sodium glucose transporter-2 inhibitors reduce the risk of major adverse cardiovascular events (MACE) in patients with type 2 diabetes mellitus and a history of atherosclerotic cardiovascular disease. Because of their baseline risk, patients with previous myocardial infarction (MI) may derive even greater benefit from sodium glucose transporter-2 inhibitor therapy. Methods: DECLARE-TIMI 58 (Dapagliflozin Effect on Cardiovascular Events–Throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 267 publications
(192 citation statements)
references
References 37 publications
4
155
0
17
Order By: Relevance
“…By contrast, in non‐HFrEF patients (either without known HF or without known reduced LVEF), HF risk reduction was lower compared with HFrEF patients and there was no effect on mortality. Yet another sub‐analysis of the same trial has demonstrated a reduction in hospitalisation irrespective of baseline CV risk profile (established CV disease or multiple risk factors), albeit individuals with prior MI derived the greatest benefit, including a reduction in the risk of 3‐point MACE with dapagliflozin …”
Section: Sodium–glucose Co‐transporter Type 2 Inhibitorsmentioning
confidence: 99%
“…By contrast, in non‐HFrEF patients (either without known HF or without known reduced LVEF), HF risk reduction was lower compared with HFrEF patients and there was no effect on mortality. Yet another sub‐analysis of the same trial has demonstrated a reduction in hospitalisation irrespective of baseline CV risk profile (established CV disease or multiple risk factors), albeit individuals with prior MI derived the greatest benefit, including a reduction in the risk of 3‐point MACE with dapagliflozin …”
Section: Sodium–glucose Co‐transporter Type 2 Inhibitorsmentioning
confidence: 99%
“…In the DECLARE–TIMI 58 study, dapagliflozin was associated with a significant reduction in the risk of CV death or hospitalization for HF (17%), but this risk reduction was the result of a reduced risk of hospitalization for HF (27%) as the risk of CV death was not significantly different (Table ) . In subgroup analyses of the DECLARE–TIMI 58 study, the risk of CV death or hospitalization for HF was reduced to a greater extent in patients with HFrEF at baseline (38%) than in those without HFrEF (12%) ( P for interaction, 0.046), while the risk of this composite outcome was consistently reduced with dapagliflozin compared with placebo in patients with or without prior MI at baseline . The greater treatment effect of dapagliflozin in patients with HFrEF may be driven by a reduction in the risk of CV death in this patient subgroup (45%) that was not observed in those without HFrEF (hazard ratio [HR] 1.08) ( P for interaction, 0.012) …”
Section: Outcomes and Sglt‐2 Inhibitorsmentioning
confidence: 99%
“…This is noteworthy considering that no such effect was established in patients who did not suffer from previous MI (HR 1.00; 95% CI, 0.88‐1.13; P = .97). A statistically significant increase in RR reduction of 31.5% for CV death or hospitalization for HF in patients with MI (1.9%) compared to patients without MI (0.6%) was noted . This effect was attributed to the increased baseline risk of adverse CV events in MI patients.…”
Section: Sglt2 Inhibitors and Diabetic Vascular Complicationsmentioning
confidence: 85%
“…A subanalysis of the DECLARE‐TIMI58 study by Furtado et al was conducted to expand upon the use of SGLT2 inhibitors in those patients who had suffered a previous MI (N = 3584) . This analysis defined two primary end points as a composite of MACE (defined by CV death, MI, or ischemic stroke) and CV death or hospitalization for HF.…”
Section: Sglt2 Inhibitors and Diabetic Vascular Complicationsmentioning
confidence: 99%